1985
DOI: 10.1016/0378-1097(85)90261-7
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation of enteric nif expression is independent of the fnr gene product

Abstract: The fnr gene product, needed for expression of anaerobic catabolism, is not needed for expression of nif in Escherichia coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2

Year Published

1987
1987
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
6
2
Order By: Relevance
“…Therefore, in addition to the rhizobial homologous Fnr proteins, FnrN and FixK, which are known to be involved in regulation of nitrogen fixation in the symbiotic bacteria (8; see reference 4 and references cited therein), in K. pneumoniae, the transcriptional activator Fnr is apparently also involved in regulation of nitrogen fixation. These results are in contrast to the report of Hill (12), that redox regulation of nif expression in a heterologous E. coli strain is independent of the E. coli fnr gene product. This discrepancy may be due to experimental differences.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, in addition to the rhizobial homologous Fnr proteins, FnrN and FixK, which are known to be involved in regulation of nitrogen fixation in the symbiotic bacteria (8; see reference 4 and references cited therein), in K. pneumoniae, the transcriptional activator Fnr is apparently also involved in regulation of nitrogen fixation. These results are in contrast to the report of Hill (12), that redox regulation of nif expression in a heterologous E. coli strain is independent of the E. coli fnr gene product. This discrepancy may be due to experimental differences.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, FNR (the fnr gene product) is the global regulator for anaerobic induction of respiratory enzyme synthesis. Since fnr mutants retain the capacity for anaerobic growth on fermentable carbon sources (Table 4), additional systems are involved in regulation of other anaerobic functions (7,160,178).…”
Section: Physiologymentioning
confidence: 99%
“…However, subsequent genetic evidence has shown that the nirA and fnr mutants have closely-linked non-complementing mutations [17]. Some of the problems associated with the nirA mutants may have been due to the presence of multiple mutations affecting anaerobic metabolism [18], and this could also explain the report that one nirA mutant is not complemented by an fnr + plasrnid [19]. Lesions in a gene designated nirR, having the same map position as fnr, and affecting the biosynthesis of nitrite reductase, nitrate reductase, cytochrome css 2, fumarate reductase, hydrogenase and formate hydrogenlyase, have also been described [20,21].…”
Section: Introductionmentioning
confidence: 99%